# Solve for x given that : 0= -(2/3)x+30

### 3 Answers | Add Yours

We have to solve 0= -(2/3)x+30

0= -(2/3)x+30

subtract 30 from both the sides

=> 0 -30 = -(2/3)x + 30 -30

=> -30 = -(2/3)x

multiply both the sides with -3/2

=> -30*(-3/2) = (-3/2)(-2/3)x

=> 90/2 = x

=> x = 45

**The equation 0= -(2/3)x+30 is in this way solved to give x = 45**

2/3x=30
3(2/3x)= 30*3
2x=90
2x/2= 90/2
x=45

u subtract 30 from both sides, you get -30=-(2/3)x

therefore, 30=(2/3)x

hence x = 30 divide by 2/3 which is 45

x=45